Celastrol targeting Nedd4 reduces Nrf2-mediated oxidative stress in astrocytes after ischemic stroke - Zexuan Hong; Jun Cao; Dandan Liu; Maozhu Liu; Mengyuan Chen; Fanning Zeng; Zaisheng Qin; Jigang Wang; Tao Tao (Elsevier, 2023)
Stroke is the second leading cause of death worldwide, and oxidative stress plays a crucial role. Celastrol exhibits strong antioxidant properties in several diseases; however, whether it can affect oxidation in cerebral ischemic-reperfusion injury (CIRI) remains unclear. This study aimed to determine whether celastrol could reduce oxidative damage during CIRI and to elucidate the underlying mechanisms. Here, we found that celastrol attenuated oxidative injury in CIRI by upregulating nuclear factor E2-related factor 2 (Nrf2). Using alkynyl-tagged celastrol and liquid chromatography-tandem mass spectrometry, we showed that celastrol directly bound to neuronally expressed developmentally downregulated 4 (Nedd4) and then released Nrf2 from Nedd4 in astrocytes. Nedd4 promoted the degradation of Nrf2 through K48-linked ubiquitination and thus contributed to astrocytic reactive oxygen species production in CIRI, which was significantly blocked by celastrol. Furthermore, by inhibiting oxidative stress and astrocyte activation, celastrol effectively rescued neurons from axon damage and apoptosis. Our study uncovered Nedd4 as a direct target of celastrol, and that celastrol exerts an antioxidative effect on astrocytes by inhibiting the interaction between Nedd4 and Nrf2 and reducing Nrf2 degradation in CIRI.